Reduction of graphene oxide/alginate composite hydrogels for enhanced adsorption of hydrophobic compounds. (17th September 2015) - Kim, Semin; Yoo, Youngjae; Kim, Hanbit; Lee, Eunju; Young Lee, Jae
Abstract: Carbon-based materials, consisting of graphene oxide (GO) or reduced GO (rGO), possess unique abilities to interact with various molecules. In particular, rGO materials hold great promise for adsorption and delivery applications of hydrophobic molecules. However, conventional production and/or usage of rGO in aqueous solution often causes severe aggregation due to its low water solubility and thus difficulties in handling and applications. In our study, to prevent the severe aggregation of GO during reduction and to achieve a high adsorption capacity with hydrophobic compounds, GO/alginate composite hydrogels were first prepared and then reduced in an aqueous ascorbic acid solution at 37 °C. Adsorption studies with a model hydrophobic substance, rhodamine B, revealed that the reduced composite hydrogels are more highly absorbent than the unreduced hydrogels. In addition, the adsorption properties of the composite hydrogels, which are consequences of hydrophobic and ionic interactions, could be modulated by controlling the degree of reduction for the adsorption of different molecules. The composite hydrogels embedding rGO can be very useful in applications related to drug delivery, waste treatment, and biosensing.